2012
DOI: 10.1111/j.1574-6941.2012.01379.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ectomycorrhizal communities in natural and cultivated Tuber melanosporum truffle grounds

Abstract: Truffles are hypogeous ectomycorrhizal (EM) fungi belonging to the genus Tuber. Although outplanting of truffle-inoculated host plants has enabled the realization of productive orchards, truffle cultivation is not yet standardized. Therefore, monitoring the distribution of fungal species in different truffle fields may help us to elucidate the factors that shape microbial communities and influence the propagation and fruiting of Tuber spp. In this study, we compared the fungal biodiversity in cultivated and na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 40 publications
(78 reference statements)
5
32
0
6
Order By: Relevance
“…Thelephoraceae species are common morphotypes on root tips in boreal forests [45] and in environments of truffle production [16,[34][35][36]39,41,47]. The genus Tomentella is widespread in orchards with Tuber spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thelephoraceae species are common morphotypes on root tips in boreal forests [45] and in environments of truffle production [16,[34][35][36]39,41,47]. The genus Tomentella is widespread in orchards with Tuber spp.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Tomentella is widespread in orchards with Tuber spp. [16,34,36,37,39,41,47]. Additionally, the species Cenococcum geophilum is a well-known cosmopolitan ectomycorrhizal fungus living in a wide range of environmental conditions [48,49] and is very abundant in truffle plantations [37].…”
Section: Discussionmentioning
confidence: 99%
“…With the appearance of the truffle brûlé at 5 to 7 years in these plantations, the management techniques shifted to reduce soil disturbance, allowing for occasional grasses and aromatic Mediterranean plants such as Thymus sp., which are supported by VAM fungi. The appearance of Glomus irregulare in the 10-year-old site and Scutellospora coralloidea at the 20-year-old site may represent the slow return of a more mixed VA-and ECM-plant community, typical of more mature truffle beds and Mediterranean open oak woodlands (Belfiori et al, 2012;Maremmani et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…As an agroforestry endeavour, cultivation of black truffles can be economically profitable in marginal farmlands, promoting increased land-use stability, 2 Inquiry into this community began with identification and morpho-typing of approximately 25 frequently observed ectomycorrhizae collected from truffle soils (Donnini & Bencivenga, 1995;Baciarelli-Falini et al, 2006) and has expanded to include 100 species of ECM fungi corresponding to 31 fungal genera (De Miguel et al, 2014). Belfiori et al (2012) observed a negative correlation between the ECM richness and the abundance of T. melanosporum mycorrhizae. The hypothesis that T. melanosporum is a dominating colonizer is supported by evidence for a decrease in the overall soil fungal diversity with the development of the truffle brûlé (Napoli et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The microbial community structures have been found to differ between natural and cultivated truffle habitats, between productive and nonproductive plantations, and between different Tuber species and developmental stages of truffles. Belfiori et al (2012) found that the diversity of ectomycorrhizal species is lower in cultivated plantations than in natural habitats, higher in Tuber brumale -colonized plants than that of T. melanosporum -colonized plants (Belfiori et al 2012), and higher in productive plantations than in the nonproductive ones (De Miguel et al 2014). In the T. magnatum natural habitats, the most abundant fungal species belong to Thelephoraceae, followed by Sebacinaceae, Inocybaceae, and Russulaceae (Murat et al 2005; Leonardi et al 2013).…”
Section: Macrofungi That Require Animals For Dispersalmentioning
confidence: 99%